Islamic Preaching Strategies in the Shiddiqiyyah Sholawat Assembly: Strategi Dakwah Islam dalam Majelis Sholawat Shiddiqiyyah - Asna Dewiyanti; Anita Puji Astutik (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Da’wah constitutes a fundamental pillar in the dissemination and internalization of Islamic teachings within society. Specific Background One form of da’wah that has grown in Indonesian Muslim communities is the majlis sholawat, which integrates devotional practices with religious education and social engagement. Knowledge Gap Although studies have examined da’wah through sholawat assemblies and religious arts, limited attention has been given to the structured strategies applied by the Shiddiqiyyah Sholawat Assembly within a local community context. Aims This study aims to analyze the da’wah strategies implemented in the Shiddiqiyyah Sholawat Assembly and to describe their role in religious life and social practices. Results Using a qualitative approach through literature study, field observation, and in-depth interviews, the findings show that the assembly applies emotional–spiritual approaches, educational activities, and social media utilization to convey Islamic messages. These strategies are associated with increased religious participation, deeper understanding of Islamic teachings, and strengthened social solidarity among participants. Novelty This study presents a contextual analysis of da’wah strategies centered on a specific sholawat assembly, highlighting the integration of spiritual expression, education, and community engagement. Implications The findings provide practical insights for da’wah practitioners and contribute to the development of adaptive Islamic preaching strategies aligned with contemporary social contexts. Keywords: Islamic Preaching, Sholawat Assembly, Da’wah Strategy, Religious Community, Qualitative Study Key Findings Highlights : Spiritual and emotional approaches shape community engagement Educational sessions support religious understanding Social activities strengthen communal solidarity